2022
DOI: 10.3389/fnagi.2022.838161
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Structural and Functional Patterns in Patients With Amnestic Mild Cognitive Impairment

Abstract: Amnestic mild cognitive impairment (aMCI) is a clinical subtype of MCI, which is known to have a high risk of developing Alzheimer’s disease (AD). Although neuroimaging studies have reported brain abnormalities in patients with aMCI, concurrent structural and functional patterns in patients with aMCI were still unclear. In this study, we combined voxel-based morphometry (VBM), amplitude of low-frequency fluctuations (ALFFs), regional homogeneity (Reho), and resting-state functional connectivity (RSFC) approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Moreover, it plays an essential role in cognitive functions, including working memory, attention, and decision-making (Carlén, 2017). In particular, there is a strong correlation between the SFGmed and the cognitive function (Li et al, 2013;Liu et al, 2022). According to our study, the decrease in GMV in the PFC is in line with that observed in previous studies, indicating that HD may exacerbate deficits in executive function of patients with ESRD.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it plays an essential role in cognitive functions, including working memory, attention, and decision-making (Carlén, 2017). In particular, there is a strong correlation between the SFGmed and the cognitive function (Li et al, 2013;Liu et al, 2022). According to our study, the decrease in GMV in the PFC is in line with that observed in previous studies, indicating that HD may exacerbate deficits in executive function of patients with ESRD.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies support our findings. For example, compared with HCs, the ALFF was decreased in the right superior frontal gyrus and right middle frontal gyrus of patients with amnestic mild cognitive impairment (aMCI) ( Liu et al, 2022 ). Another study found that patients with aMCI had decreased ALFF values in the posterior cingulate/precuneus, medial prefrontal cortex, hippocampus/ parahippocampal gyrus, basal ganglia, and prefrontal regions, while ALFF values in several regions of the occipital and temporal lobe were higher compared with the NC group ( Han et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it presented unabiding and region-specific cholinergic neuroplastic reactions (Ikonomovic et al, 2007 ). Therefore, the SFG could be the major region consisting of various cognitive deficits in MCI, in structural and functional aspects (Liu et al, 2022 ). Besides, attenuated spontaneous neuronal activities of the SFG.R could identify MCI patients from HCs.…”
Section: Discussionmentioning
confidence: 99%